The Relationship between Breakfast Habits and Learning Concentration of Elementary School Students - Christiana, Ananda Ekka; Abiddin, Andi Hayyun; Martiningsih, Wiwin (Health Access Journal, 2024)
Breakfast habit is an activity of eating and drinking in the morning before activities carried out > 4 times in one week. Although breakfast has an important role in supporting activities, many school children do not or rarely have breakfast. This study aims to analyze the relationship between breakfast habits and learning concentration of elementary school students at Kedungcangkring State Elementary School 1. This study used a type of quantitative research with a cross sectional research design. The population in this study amounted to 66 students and the sample amounted to 35 respondents using purposive sampling. The measuring instruments used were questionnaires and grid concentration tests. The analysis used is spearman rank correlation. The results showed that all had good and sufficient breakfast habits. More than half of the students have good and sufficient learning concentration. The results of cross tabulation showed that out of 35 respondents more than half of the students had good breakfast habits with good concentration (54.39%). The statistical test results show a significant value of p-value = 0,000 (<0,05) with a value of r=0.865 which means there is a relationship between breakfast habits and learning concentration of elementary school students at Kedungcangkring State Elementary School 1. It is hoped that this research can be a guideline for institutions in providing counseling on the importance of breakfast for school children and for parents to always provide breakfast with different menus every day.